Soybean oil and residual soybean oil in diets for feedlot sheep: Blood parameters - Scarpino, F. B.O. [UNESP]; Ezequiel, J. M.B. [UNESP]; Silva, D. A.V. [UNESP]; e van Cleef, E. H.C.B. (SciELO Espana/Repisalud, 2014)
The objective of this study was to evaluate the effects of 2 dietary lipid sources (soybean oil and residual soybean oil) on blood parameters of feedlot sheep. It were used 24 male lambs Santa Inês × Dorper, uncastrated, distributed in a randomized block design and assigned to three experimental diets: C= control diet, composed by forage concentrate ratio of 40:60, S= C with 6 % of soybean oil, and R= C with 6 % of frying oil. Corn silage was the roughage and concentrate was composed by whole corn grain, soybean hulls, sunflower meal, urea, mineral salt, limestone, and antioxidant. The animals were kept in individual pen for 105 days, and at day 59 blood samples were collected by jugular vein puncture for quantification of glucose, triglycerides, cholesterol, total protein, and liver enzymes AST (aspartate aminotransferase), GGT (gamma glutamyl transferase) and FAL (alkaline phosphatase). Inclusion of 6 % of soybean oil or frying oil in diet increased the concentration of cholesterol and AST (p<0.01); FAL tended (p= 0.06) to increase when residual oil was used. However, such changes are not sufficient to cause damage to animal health.
Óleo de soja e óleo de soja residual em dietas para ovinos confinados: Parâmetros sanguíneos
Keywords: Alternative feed; Blood; Lambs